2016
DOI: 10.1073/pnas.1522434113
|View full text |Cite
|
Sign up to set email alerts
|

Fuxianhuiid ventral nerve cord and early nervous system evolution in Panarthropoda

Abstract: Panarthropods are typified by disparate grades of neurological organization reflecting a complex evolutionary history. The fossil record offers a unique opportunity to reconstruct early character evolution of the nervous system via exceptional preservation in extinct representatives. Here we describe the neurological architecture of the ventral nerve cord (VNC) in the upper-stem group euarthropod Chengjiangocaris kunmingensis from the early Cambrian Xiaoshiba Lagerstätte (South China). The VNC of C. kunmingens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
142
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(152 citation statements)
references
References 51 publications
6
142
1
Order By: Relevance
“…This includes the recent high-profile interpretations of neural and vascular tissues in Burgess Shale-type preserved ecdysozoans20212223242526. An inconsistency is identified between those anatomical interpretations and current understanding of preservation.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the recent high-profile interpretations of neural and vascular tissues in Burgess Shale-type preserved ecdysozoans20212223242526. An inconsistency is identified between those anatomical interpretations and current understanding of preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [102] identified well organized segmental ganglia in a total group euarthropod from the Chengjiang biota. Sansom [18] argued that this interpretation was implausible based on the rapid loss of nervous system morphology in his decay experiments on priapulids.…”
Section: Decay Induced Distortions Are Not Characteristic Of Exceptiomentioning
confidence: 99%
“…Sansom [18] argued that this interpretation was implausible based on the rapid loss of nervous system morphology in his decay experiments on priapulids. However, it is difficult to conceive how shrinkage of other anatomical features could generate the wellorganized features [103][104][105] and serially repeated structures [102] interpreted as fossil nervous systems. Shrinking a cuticle would not be expected to generate a rope-ladder morphology that was the primary basis for identification as a nerve cord.…”
Section: Decay Induced Distortions Are Not Characteristic Of Exceptiomentioning
confidence: 99%
“…1) -represent a critical resource for studying the ancient biosphere. Fossils of this type include some of the earliest organisms on Earth (Knoll, 1985) as well as remains of integuments (Manning et al, 2009;Navalón et al, 2015), exoskeletons (McNamara et al, 2012a), feathers (Colleary et al, 2015), eyes (Lee et al, 2011), muscles (Martill, 1990), "jellies" (Chen et al, 2007;Stanley and Sturmer, 1987), internal organs (Zhang et al, 2015), nerves (Yang et al, 2016), cells (Xiao et al, 1998), and sub-cellular structures , which offer many opportunities for work on anatomy, physiology, and systematics. Furthermore, geologic deposits containing exceptionally-preserved fossils-such as certain Konservat-Lagerstätten (Seilacher, 1970)-offer relatively complete snapshots for exploring the ecology and dynamics of ancient ecosystems, as they generally contain remains of both biomineralizing and non-mineralizing taxa (Conway Morris, 1986).…”
Section: Introductionmentioning
confidence: 99%